2021
DOI: 10.1002/mds.28624
|View full text |Cite
|
Sign up to set email alerts
|

Cortical [18F]PI‐2620 Binding Differentiates Corticobasal Syndrome Subtypes

Abstract: Background Corticobasal syndrome is associated with cerebral protein aggregates composed of 4‐repeat (~50% of cases) or mixed 3‐repeat/4‐repeat tau isoforms (~25% of cases) or nontauopathies (~25% of cases). Objectives The aim of this single‐center study was to investigate the diagnostic value of the tau PET‐ligand [18F]PI‐2620 in patients with corticobasal syndrome. Methods Forty‐five patients (71.5 ± 7.6 years) with corticobasal syndrome and 14 age‐matched healthy controls underwent [18F]PI‐2620‐PET. Beta‐am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
51
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 46 publications
12
51
2
2
Order By: Relevance
“…The 18 F‐florzolotau PET findings presented herein also support an increased tracer uptake in subcortical regions of patients with CBS—a pattern with similarities to PSP 9 . On analyzing 18 F‐PI‐2620 signals in patients with CBS and PSP‐RS, Palleis and colleagues 8 reported distinct findings for the two conditions—with the former being characterized by an increased tracer uptake in the putamen and external GP and the latter in the internal GP, STN, and substantia nigra. However, our observations did not show obvious differences in terms of positivity or negativity ratios but were limited to quantitative analysis.…”
Section: Discussionsupporting
confidence: 71%
“…The 18 F‐florzolotau PET findings presented herein also support an increased tracer uptake in subcortical regions of patients with CBS—a pattern with similarities to PSP 9 . On analyzing 18 F‐PI‐2620 signals in patients with CBS and PSP‐RS, Palleis and colleagues 8 reported distinct findings for the two conditions—with the former being characterized by an increased tracer uptake in the putamen and external GP and the latter in the internal GP, STN, and substantia nigra. However, our observations did not show obvious differences in terms of positivity or negativity ratios but were limited to quantitative analysis.…”
Section: Discussionsupporting
confidence: 71%
“…CBS patients (Palleis et al, 2021). In that study, a clear hemispheric asymmetry was observed in binding and correlated well with symptom dominant side.…”
Section: Discussionsupporting
confidence: 52%
“…Patients with 4R-tauopathies (PSP and CBS) were assessed by the PSP rating scale. Tau-PET analysis and separate analysis of early-phase imaging of both tracers were reported in previous investigations [ 9 , 13 , 23 – 25 ]. The control cohort ( n = 15) was selected from previous studies [ 13 , 23 ].…”
Section: Methodsmentioning
confidence: 79%
“…Tau-PET analysis and separate analysis of early-phase imaging of both tracers were reported in previous investigations [ 9 , 13 , 23 – 25 ]. The control cohort ( n = 15) was selected from previous studies [ 13 , 23 ]. All controls had negative amyloid- and tau-PET scans (visual read) and a Fazekas score ≤ 1.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation